Species Distribution and Antifungal Susceptibility of Candida spp. responsible for Pulmonary Candidiasis - Suhartono Suhartono; Wilda Mahdani; Rajuliana Rajuliana (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2021)
Fungal infection can occur in almost all parts of the human body, including the respiratory system. One group of fungi causing opportunistic infections in the lungs also known as pulmonary candidiasis is Candida spp. This study aimed to determine species diversity and antifungal sensitivity of Candida sp. causing pulmonary candidiasis from sputum specimen isolates in the Zainoel Abidin Hospital (ZAH). The sputum specimens were from inpatients and outpatients during a period of January 2019 to January 2021. Identification of Candida spp. and the antifungal sensitivity were carried out using culture and Gram Staining as well as the VITEK® 2 Compact. The results of this study indicated that there were six species of Candida sp. obtained from the study period. Of total 73 isolates, the highest percentage of species was Candida albicans (56.16%). The percentage of pulmonary candidiasis based on age was dominated by the early-late age category 46-65 years (50.68%) and based on sex was dominated by men (71.23%). Antifungal susceptibility assays revealed that the Candida species remained highly susceptible to the antifungals (amphotericin B, caspofungin, flucytosine, fluconazole, micafungin, and voriconazole), i.e., greater than 91 percent. Overall, the results of this study indicated that pulmonary candidiasis were predominantly related to C. albicans and C. tropicalis infections in ZAH and the sensitivity of antifungal drugs remained empirically and definitively effective. This research might be important as a part of infection prevention and control strategies, as well as the administration of empirical antifungals to combat Candida-mediated lung infections.